PHARMACEUTICAL LIPOSOMAL DRUG DELIVERY: A COMPLETE REVIEW OF NEW DELIVERY SYSTEM - Maurya, Priyanka; Gupta, Kirti; Kushwaha, Ashutosh; Mishra, Dr Jai Narayan (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2021)
When a self-forming enclosed lipid bi-layer was hydrated, the liposome or lipid vesicle was discovered. Liposome drug delivery systems have played a key role in the development of powerful drugs that have improved therapies Liposome formulations have recently been aimed at reducing toxicity and increasing accumulation at the target site The suppression of rapid liposome clearance by regulating particle size, charge, and surface hydration is one of several new liposome manufacturing methods based on lipid drug interactions and liposome disposition mechanisms. Targeting tissue with or without expression of target recognition molecules on the lipid membrane is the most common clinical use of liposomal drug delivery. Physical, chemical, and biological factors are used to characterise the liposomes. Liposome size is another important metric that helps describe the liposome, which is normally done by successive extrusion at different temperatures. Several groups of medications, such as antiviral, antifungal, antibacterial, vaccines, anti-tubercular therapies, and gene treatments, benefit from this route of drug delivery since it increases their safety and efficacy. Liposomes are now used in immunology, dermatology, vaccine adjuvant, eye problems, brain targeting, infectious disease, and cancer therapy. The particular binding properties of a drug-carrying liposome to a target cell, such as a tumour cell, and certain substances in the body (antibodies, proteins, peptides, and so on) are recent breakthroughs in this field; stealth liposomes, which are notably being exploited as carriers for hydrophilic drugs (water soluble) anticancer drugs like doxorubicin, mitoxantrone; and bisphosphonate- liposome mediated depletion of macrophages. This review would be a help to the researchers working in the area of liposomal drug delivery.